TBX18 transcription factor overexpression in human‐induced pluripotent stem cells increases their differentiation into pacemaker‐like cells. Issue 2 (5th August 2018) - Gorabi, Armita M.; Hajighasemi, Saeideh; Tafti, Hossein A.; Atashi, Amir; Soleimani, Masoud; Aghdami, Nasser; Saeid, Ali K.; Khori, Vahid; Panahi, Yunes; Sahebkar, Amirhossein
Abstract : Background: The discovery of gene‐ and cell‐based strategies has opened a new area to investigate novel approaches for the treatment of many conditions caused by cardiac cell failure. The TBX18 (T‐box 18) transcription factor is considered as a prominent factor in the sinoatrial node (SAN) formation during the embryonic development. In this in vitro study, the effect of TBX18 gene expression on human‐induced pluripotent‐stem‐cell‐derived cardiomyocytes (hiPS‐CMs) to induce pacemaker‐like cells was examined. Methods: The human‐dermal‐fibroblast‐derived iPSCs were transfected using chemical, physical, and Lentiviral methods of TBX18 gene delivery during differentiation into cardiomyocytes (CMs). After the differentiation process through small‐molecule‐based temporal modulation of the Wnt signaling pathway, the hiPSC‐CMs were analyzed using the real‐time polymerase chain reaction, immunocytochemistry, immunofluorescence, whole‐cell patch‐clamp recording, and western blotting to investigate the accuracy of differentiation and identify the effect exerted by TBX18. Results: The hiPS‐CMs showed spontaneous beating and expressed specific markers of cardiac cells. The lentiviral‐mediated TBX18 delivery was the most efficient method for transfection. The results showed the increment in Connexin 43 expression among untransfected hiPS‐CMs, whereas this protein was significantly downregulated followed by TBX18 overexpression. TBX18‐hiPSCMs were detected with pacemaker cell features. Conclusions: It was demonstrated that the TBX18 gene is able to conduct hiPSCs to differentiate into pacemaker‐like cells. The TBX18 gene delivery seems to have the potential for the development of biological pacemakers; however, more investigations are still needed to assess its usefulness to fix arrhythmic conditions with SAN failure basis. Abstract : In this in vitro study, the effect of T‐box 18 gene expression in human‐induced pluripotent‐stem‐cell‐derived cardiomyocytes to induce pacemaker‐like cells was examined.